PELATIHAN PENGGUNAAN QUILLBOLT PADA GURU-GURU MTs DARUL HIKMAH - Yuliani, Sri; Anisa, Bismi; Hartanto, Dicki; Istikomah, Endang; Marhamah, Marhamah; Yulianto, Yulianto (LPPM Universitas Bina Bangsa, 2024)
The needs for teachers to be promoted by creating scientific articles requires fast AI media to help paraphrase sentences to avoid plagiarism. Especially teachers at MTs Darul Hikmah Pekanbaru Riau, most of whom are applying for their promotion so that AI Quillbolt is a media to help avoid plagiarism so that training is needed to use Quillbolt paraphrasing with the aim of three main factors, namely: increasing (1) teachers' knowledge about Quillbot, which is able to identify and implement existing technology in the field of education (2) The second component, partner teachers where the insight, ability of teachers in this school understands the reasons for mastering renewable technology for the implementation of efficiency and effectiveness in the school system and (3) The third component is that partner teachers in this school have the ability to take action in certain situations with the aim of building ideas about the focus of using renewable technology for school progress with responsive behavior to environmental situations, understanding events, and then evaluating the existing educational technology system and has been mastered verbally and in writing. From this community service activity, it was found that the teachers had mastered the use of Quilbolt paraphrasing to prepare articles that would be used as material for their promotion, so this Quilbolt AI was very helpful to them